2014
DOI: 10.1089/tmj.2013.0045
|View full text |Cite
|
Sign up to set email alerts
|

Streamlining HIV Testing in the Emergency Department—Leveraging Kiosks to Provide True Universal Screening: A Usability Study

Abstract: ED patient response to the kiosk system was favorable. Subjects easily and quickly navigated the program, with the exception of a login screen, which could be eliminated via automated login using ID bracelet scanners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The calibration curve from our analysis actually demonstrates this, i.e. 24 the expected HIV seropositivity was slightly lower than the observed one in patients, especially in those with lower risk score (Figure 2A). Novel risk assessment via touch-screen kiosk or tablet could significantly reduce this type of information bias.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The calibration curve from our analysis actually demonstrates this, i.e. 24 the expected HIV seropositivity was slightly lower than the observed one in patients, especially in those with lower risk score (Figure 2A). Novel risk assessment via touch-screen kiosk or tablet could significantly reduce this type of information bias.…”
Section: Discussionsupporting
confidence: 57%
“…Novel risk assessment via touch-screen kiosk or tablet could significantly reduce this type of information bias. 24 Third, the HIV screening programmatic data come from two geographically close EDs under the same hospital and health system. These two urban EDs are located in a high HIV/AIDS prevalence city where several large-scale HIV intervention programs have been implemented.…”
Section: Discussionmentioning
confidence: 99%
“…16 Of the patients infected with HIV, approximately 27% had not received a diagnosis (Figure) compared with 14% nationally, 4 confirming the importance of ongoing HIV screening in EDs. Although different approaches of identifying patients for ED-based testing continue to be evaluated and the optimal screening approach remains uncertain, 1720 testing for HIV infection, irrespective of the screening approach, remains the critical first step in a series of important interventions aimed at reducing the burden of HIV disease. Identifying such individuals with HIV infection provides a critical opportunity to link them to care in which treatment slows disease progression and reduces infectivity.…”
mentioning
confidence: 99%
“…We implemented a kiosk-facilitated screening program at registration to engage and offer patients HIV testing, following the success of our prototype system as a means of offering HIV testing to ED patients (Orlando et al, 2014; Rothman et al, 2014). Our results demonstrated that a kiosk-driven program increased numbers of engagement of higher-risk patients for testing (Hsieh et al, 2014).…”
mentioning
confidence: 99%